Social life for sale! A critical discourse analysis of the concept of student life on Danish university websites. Issue 4 (4th July 2018) - Svendsen, Jesper Tinggaard; Svendsen, Annemari Munk
ABSTRACT: This paper aims to investigate the marketization of higher education (HE) as it manifests itself in the concept of Student life on Danish HE websites. Taking Norman Fairclough's critical discourse analysis as its starting point, this paper critically examines this particular practice of marketization by making a single-case study of the pages called Student life at the biggest university in Denmark, Copenhagen University (CU). The findings show that these page elements of social life are intensively and routinely used to soften up the more demanding aspects of being a university student, and that this involves a significant positive evaluation of life as a university student. The paper addresses the potential problems related to the findings in order to contribute to further discussion and reflection upon issues centred around the marketization of HE on university websites and around the construction of what it means to be a student today.